2021
DOI: 10.1111/jvim.16234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cardiac troponin‐I concentrations for diagnosis of infective endocarditis in dogs

Abstract: Background Infective endocarditis (IE) in dogs is associated with severe disease and a high case fatality rate but often presents with nonspecific clinical signs. Hypothesis/Objectives Serum concentration of cardiac troponin‐I (cTnI) is elevated in dogs with IE and can differentiate dogs with IE from dogs with other diseases with similar clinical features. Concentration of serum cTnI is negatively correlated with survival time in dogs with IE. Animals Seventy‐two client‐owned dogs; 29 with IE, 27 with stage‐B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…and Pasteurella spp., which have all been reported in previous USA studies (MacDonald et al 2004, Sykes et al 2006a, Reagan et al 2022. The mitral valve was most commonly infected in this study as shown in recent studies (Kilkenny et al 2021;Reagan et al 2022). This differs from previous studies however where both the aortic and mitral valve were frequently affected (Sykes et al 2006a).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…and Pasteurella spp., which have all been reported in previous USA studies (MacDonald et al 2004, Sykes et al 2006a, Reagan et al 2022. The mitral valve was most commonly infected in this study as shown in recent studies (Kilkenny et al 2021;Reagan et al 2022). This differs from previous studies however where both the aortic and mitral valve were frequently affected (Sykes et al 2006a).…”
Section: Discussionsupporting
confidence: 86%
“…The mean age at which dogs were infected with IE in this study was similar in males and in females. A higher proportion of middle-aged to older dogs were reported with IE in this study as noted in previous studies (Sisson & Thomas 1984, Sykes et al 2006b, Kilkenny et al 2021, Reagan et al 2022. This may be due to age-related senescence of the immune system, which has been shown to increase the incidence of infection in older pets (Day 2010).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations